Gradescope in Large Lecture Classrooms: A Case Study at Indiana University - Carrie A. Hansel; Anne Ottenbreit-Leftwich; Joshua D. Quick; Anna Hungerfield Greene; Maggie Ricci (Journal of Teaching and Learning with Technology, 2024)
This qualitative, multi-case study explores how instructors at one higher education institution used an emerging technology, Gradescope, in their large classes to support the assessment of student learning. The study examines the practices of two instructors who taught large lecture classes with more than 100 students and used Gradescope to assist with the assessment of student learning. Results indicate that using Gradescope helped the instructors overcome specific challenges associated with large lecture courses, such as grading a large volume of assignments, , providing timely feedback, and maintaining grading consistency across large numbers of students and graders. Course DFW rates decreased and average course grades increased during the semester where the instructors used Gradescope. Instructors reported increased grading efficiency and improved student satisfaction. However, the use of Gradescope is not entirely responsible for the positive impacts. Instructors also described adapting their teaching methods and assessment strategies to integrate Gradescope effectively.